Acute carpal tunnel syndrome in a patient with haemophilia. (3rd July 2012) - Mayne, Alistair Ivan William; Howard, Anthony; Kent, Matthew; Banks, Joanne
Abstract : Acute carpal tunnel syndrome (CTS) is a rare surgical condition usually resulting from wrist trauma. We present the case of a young haemophilic man who developed acute CTS following trivial injury. The patient was initially managed conservatively but symptom progression resulted in carpal tunnel decompression. A literature review and management approach are presented. This is an important complication of haemophilia to be aware of as prompt conservative management can obviate the need for surgery. This case is useful in (a) highlighting the importance of considering a patient's medical history when formulating differential diagnoses and (b) outlining a management approach to this condition.